2018
DOI: 10.3354/esr00875
|View full text |Cite
|
Sign up to set email alerts
|

Communicating amidst the noise: modeling the aggregate influence of ambient and vessel noise on baleen whale communication space in a national marine sanctuary

Abstract: Anthropogenic noise negatively impacts many species. One of the more insidious effects of elevated noise levels is the reduction in area over which animals are able to acoustically communicate, often termed communication masking. This study utilizes modeling approaches to evaluate relative levels of masking for 4 baleen whale species from the combination of current ambient noise conditions and noise from discrete vessels operating in the Stellwagen Bank National Marine Sanctuary. Acoustic data were collected u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 58 publications
1
49
0
2
Order By: Relevance
“…There is potential for disturbance of breeding and resting behavior, masking of communication, and even physiological damage if in close proximity or with long exposures of cetaceans to loud anthropogenic noises. Numerous studies on a variety of cetacean species globally have documented behavioral responses, such as changes in travel routes and distribution, and shifts in vocal display behavior to seismic airguns, echo sounders, navy sonar and ship noise (Nowacek et al, 2007;Castellote et al, 2012;Cerchio et al, 2014;Cholewiak et al, 2018). It has also been shown that noise from petroleum E&P activities and vessel traffic contributes significantly to ambient noise within the communication bandwidth of baleen whales, likely acting to mask communication and breeding displays (Clark et al, 2009;Cholewiak et al, 2018).…”
Section: Petroleum Exploration and Production (Eandp)mentioning
confidence: 99%
“…There is potential for disturbance of breeding and resting behavior, masking of communication, and even physiological damage if in close proximity or with long exposures of cetaceans to loud anthropogenic noises. Numerous studies on a variety of cetacean species globally have documented behavioral responses, such as changes in travel routes and distribution, and shifts in vocal display behavior to seismic airguns, echo sounders, navy sonar and ship noise (Nowacek et al, 2007;Castellote et al, 2012;Cerchio et al, 2014;Cholewiak et al, 2018). It has also been shown that noise from petroleum E&P activities and vessel traffic contributes significantly to ambient noise within the communication bandwidth of baleen whales, likely acting to mask communication and breeding displays (Clark et al, 2009;Cholewiak et al, 2018).…”
Section: Petroleum Exploration and Production (Eandp)mentioning
confidence: 99%
“…It remains to be seen whether the adjustments in calling behavior observed in this study are indicative of a compensatory strategy to overcome masking, or whether the reduction in calling effort is a result of missed cues from other vocalizing whales. In the absence of vocal compensation, increased ambient noise levels substantially reduce the active communication space of a calling animal (Cholewiak et al 2018, Gabriele et al 2018. Even relatively short periods of high noise, like those observed during the twice-daily cruise ship passages, may 'halt the conversation' to unknown effect.…”
Section: Probability Of Occurrencementioning
confidence: 99%
“…A decrease in communication range as a result of increased levels of ship noise has also been modeled for Bryde's (Balaenoptera edeni), fin (Balaenoptera physalus), humpback, and minke whales (Balaenoptera acutorostrata) Cholewiak et al, 2018;Gabriele et al, 2018;Putland et al, 2018). The Lombard effect comprises changes in the spectral features of vocalizations (i.e., in frequency and level) and in vocalization rates, in order to compensate for masking (Lombard, 1911).…”
Section: Mysticetesmentioning
confidence: 99%